Tough love : sexuality, compassion, and the Christian right - Burack, Cynthia, 1958- (SUNY series in queer politics and cultures., 2014)
"Exposes how ex-gay and post-abortion ministries operate on a shared system of thought and analyzes their social implications"--Provided by publisher